2023
DOI: 10.3390/ijms241914561
|View full text |Cite
|
Sign up to set email alerts
|

Turmeric and Curcumin—Health-Promoting Properties in Humans versus Dogs

Jagoda Kępińska-Pacelik,
Wioletta Biel

Abstract: The growing popularity of the use of nutraceuticals in the prevention and alleviation of symptoms of many diseases in humans and dogs means that they are increasingly the subject of research. A representative of the nutraceutical that deserves special attention is turmeric. Turmeric belongs to the family Zingiberaceae and is grown extensively in Asia. It is a plant used as a spice and food coloring, and it is also used in traditional medicine. The biologically active factors that give turmeric its unusual prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 169 publications
0
3
0
Order By: Relevance
“…Following the optimization of the oil volume fraction and the homogenization speed, it was important to understand whether CMC-GA particles of varying pH levels can yield a stable Pickering emulsion. In order to address this, CMC-GA colloidal particles of varying pH levels (3)(4)(5)(6)(7)(8)(9) were used to emulsify coconut oil in water, using previously optimized conditions (an oil volume fraction of 0.6 and a homogenization speed of 16,000 rpm). The stability of the resulting emulsion was monitored by assessing the phase separation, oil droplet size, and viscosity.…”
Section: Effect Of Ph On the Stability Of The Cmc-ga-emulsified Picke...mentioning
confidence: 99%
See 1 more Smart Citation
“…Following the optimization of the oil volume fraction and the homogenization speed, it was important to understand whether CMC-GA particles of varying pH levels can yield a stable Pickering emulsion. In order to address this, CMC-GA colloidal particles of varying pH levels (3)(4)(5)(6)(7)(8)(9) were used to emulsify coconut oil in water, using previously optimized conditions (an oil volume fraction of 0.6 and a homogenization speed of 16,000 rpm). The stability of the resulting emulsion was monitored by assessing the phase separation, oil droplet size, and viscosity.…”
Section: Effect Of Ph On the Stability Of The Cmc-ga-emulsified Picke...mentioning
confidence: 99%
“…Furthermore, curcumin also suppresses solar UV ray-induced inflammatory responses by inhibiting the activation of NF-κB and other pro-inflammatory transcription factors [ 2 , 3 ]. Moreover, curcumin is reported for a wide range of medicinal properties, and is also very well tolerated by the human body, even up to 8 g a day, without showing any significant toxicity symptoms [ 4 , 5 , 6 , 7 ]. All these facts have prompted researchers to develop curcumin-based cosmetic formulations, such as sun-screening cream or for general skin care applications [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“… 57 Turmeric and curcumin, known for their anti-inflammatory and antioxidant properties, may also offer some protective benefits. 58 It is reported that compared to the omega-6 arachidonic acid, marine omega-3 fatty acids such as eicosapentaenoic acid and docosahexaenoic acid have demonstrated a lower associated risk of BC. Regular exercise is also crucial in this context.…”
Section: Introductionmentioning
confidence: 99%